Implementation Implementation of Ideal Parenting in the Qur'an for Students of SMPIT Darul Qur’an Bogor: Studi Living Quran - Ghoni, Abdul Ghoni; Sumayyah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
One of the reasons for wrong behavior by a child is that the parenting style implemented by the parents is not working well. Therefore, this research was conducted to find solutions for ideal parenting patterns that refer to the Quran. The research method used is mixed methods, which combines qualitative research related to parenting models in the Quran and quantitative approaches to determine the level of implementation in social reality. The results of this research show that there are four parenting patterns for parents towards their children: by building good communication, using calls that honor the child, conveying the consequences of mistakes and cultivating an attitude so that the child is respectful to both parents. This research has 108 respondents of students’ parents of SMPIT Darul Quran Bogor. It concludes that parents have a level of implementation of good communication parenting patterns with the highest percentage of 27%, and the lowest implementation in parental cultivation is in the process of instilling the consequences of bad deeds morals so that children are respectful to their parents, amounting to 23%. These findings indicate that maximum efforts are needed to ensure that children have good character to their parents by informing them of the consequences.